Adjunct effect of music therapy on cognition in Alzheimer’s disease in Taiwan: a pilot study - Li CH (Dove Medical Press, 2015)
Chien-Hsun Li,1–3 Ching-Kuan Liu,2,3 Yuan-Han Yang,2–4 Mei-Chuan Chou,2,4 Chun-Hung Chen,2 Chiou-Lian Lai2,3 1Department of Neurology, Kaohsiung Municipal Hsiao-Kang Hospital, Kaohsiung Medical University, Kaohsiung, Taiwan; 2Department of Neurology, Kaohsiung Medical University Hospital, Kaohsiung, Taiwan; 3Department of and Master’s Program in Neurology, School of Medicine, College of Medicine, Kaohsiung Medical University, Kaohsiung, Taiwan; 4Department of Neurology, Kaohsiung Municipal Ta-Tung Hospital, Kaohsiung, Taiwan Purpose: Music therapy (MT) reviews have found beneficial effects on behaviors and social interaction in Alzheimer’s disease (AD) but inconsistent effects on cognition. The purpose of the study was to evaluate the adjunct effect of long-term and home-based MT in AD patients under pharmacological treatment. Patients and methods: Mild AD cases (clinical dementia rating =0.5~1) were consecutively recruited and voluntarily separated into an MT group or control group (CG) for 6 months. Outcome assessments included Cognitive Abilities Screening Instrument (CASI), CASI-estimated mini-mental state examination, clinical dementia rating with sum of box scores, and neuropsychiatric inventory. The MT interventions were Mozart’s Sonata (KV 448) and Pachelbel’s Canon, listening with headphones for 30 minutes daily in the morning and before sleep, respectively. Results: Forty-one cases (MT versus CG number =20 versus 21) were analyzed. Adjusted differences of CASI-estimated mini-mental state examination and CASI after 6 months in the MT group were slightly less decreased than the CG without statistical significance. In further analysis of cognitive domains of CASI, the adjusted difference of abstraction domain in the MT group was significantly better than the CG. Conclusion: Although there were no apparent additional benefits of this MT on the global cognition and daily functioning in mild AD patients, it confirms the adjunct cognition effect on the abstraction. This MT contributes to the supplementary treatment of AD. Keywords: abstraction, behavioral and psychological symptoms of dementia, cross-cultural effect, Mozart effect, non-pharmacological intervention, supplementary treatment